2020
DOI: 10.1037/ser0000333
|View full text |Cite
|
Sign up to set email alerts
|

Predicting attrition in long-term residential substance use disorder treatment: A modifiable risk factors perspective.

Abstract: Although numerous factors are associated with attrition in substance use disorder (SUD) treatment, many are unmodifiable and therefore difficult to target in efforts to improve treatment outcomes. The current study sought to identify the strongest and most modifiable predictors of attrition in long-term residential SUD treatment from myriad characteristics associated with treatment termination. Archival data were examined for 2,069 adults (74% male; 38% non-Hispanic White) who entered a long-term residential S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
(100 reference statements)
2
10
0
1
Order By: Relevance
“…Moreover, more than half of the patients did not achieve their therapeutic objectives. This number is slightly higher than that observed by Baker et al [31] and is in line with other results found in observational studies [3,14]. These dropout rates highlight the therapeutic complexity of TC treatment for patients with SUD.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, more than half of the patients did not achieve their therapeutic objectives. This number is slightly higher than that observed by Baker et al [31] and is in line with other results found in observational studies [3,14]. These dropout rates highlight the therapeutic complexity of TC treatment for patients with SUD.…”
Section: Discussionsupporting
confidence: 89%
“…Consequently, it has been possible to provide more precise statistical estimates [19]. Moreover, unlike another study that used EHR data [31], we analyzed the impact of mental disorders diagnosed according to ICD-10 criteria, one of the most widely used nosological classifications in the clinical context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While demographic factors such as race (Black; White et al, 2016) and low education (White et al, 2016), may partly explain the differential study follow‐up completion rates among drug users and non‐users, there are other reasons as well. For example, among adults who use illicit drugs, the transitory nature of the population, having unstable accommodation, and having no access to phones are potential reasons for drop‐out (Baker et al, 2019). Further, the transtheoretical model of change (TTM), based on the process of individuals′ decision making to effect change, has been used as the framework for behavioral modification to explain why some individuals are successful and others are not in treating various psychological or health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients drop out in advanced stages of treatment and represent a great loss due to the health resources consumed. According to the evidence, after 37.37 days of treatment there is a reliable change in psychological recovery and well-being [64] and, in the case of late dropouts, shorter residential treatment with longer aftercare may be beneficial [65], both in terms of cost and clinical outcomes [66]. On the other hand, late dropouts could also be subjected to a pre-treatment phase to improve the stage of change, which has been shown to be a good predictor of treatment completion [67].…”
Section: Discussionmentioning
confidence: 99%